Pharmacokinetics of intravenous cefetamet and oral cefetamet pivoxil in children. - Hayton, W L (1991)
The pharmacokinetics of cefetamet were determined after intravenous (i.v.) administration of cefetamet and oral administration of cefetamet pivoxil syrup to patients between the ages of 3 and 12 years. The patients were hospitalized for reconstructive urological surgery; to prevent infection, prophylactic i.v. cefetamet was administered on the day of surgery and oral cefetamet pivoxil was administered 2 days later. After i.v. administration, the mean (+/- standard deviation) half-life of cefetamet was 1.97 +/- 0.60 h (n = 18), which was different from the 2.46 +/- 0.33 h reported for nine adults (22 to 68 years old) in a previous study. The average values for the mean residence times were 2.35 +/- 0.94 and 2.83 +/- 0.34 h and the average values for the fraction of the dose eliminated unchanged in the urine were 79.9% +/- 8.99% and 80% +/- 11% in children and adults, respectively. Plots of mean systemic clearance and steady-state volume of distribution versus body weight for the children and comparative adults were linear on log-log coordinates, and the slopes of the plots were 0.661 and 0.880, respectively. These slope values suggested that mean systemic clearance values per unit of body surface area were similar in children and adults and that maintenance doses for children should be the adult maintenance dose multiplied by the child's surface area divided by 1.73 m2. The mean (+/- standard deviation) oral bioavailabilities of cefetamet pivoxil were 49.3% +/- 15.7% in 3- to 7-year-old children who received a 500-mg dose and 37.9% +/- 10.0% in 8- to 12-year-old children who received a 1,000-mg dose. These values were not different from that observed in the adult group after two 500-mg tablets. Likewise, the peak concentration of cefetamet in plasma and its time of occurrence in children were in line with the values which have been observed for adults.